Three Dogmas of Normativity. Issue 2 (1st November 2022) - Chang, Ruth
ABSTRACT: In this article, I identify and critically examine 3 dogmas of normativity that support a commonly accepted 'Passivist View' of rational agency. I raise some questions about these dogmas, suggest what we should believe in their place, and moot an alternative 'Activist View' of what it is to be a rational agent that grows out of rejection of the 3 dogmas. Underwriting the dogmas and the Passivist View, I suggest, is a deeply held but mistaken assumption that the normative domain is fundamentally akin to the nonnormative domain. Once we allow that the normative may be fundamentally unlike the nonnormative in certain key ways, a shift in our thinking about what it is to be rational becomes possible. I end by considering some implications of this paradigm shift in rationality from the passive to the active for various applied matters.